Percepção da paisagem por meio da arte: o papel da FAOP na cidade de Ouro Preto/MG (1960-2020) - Gabriela Lopes de Moura Rangel (2024)
The research Perception of landscape through art: the role of FAOP in the city of Ouro Preto (1960-2020) takes place at the meeting point of the fields of landscape and art history, teaching and artistic practice in Ouro Preto/MG, a Cultural Heritage of Humanity city. It begins with the creation of the Fundação de Arte de Ouro Preto/FAOP in 1968 and studies the landscape of Ouro Preto from the point of view of leading artists and those linked to the history of the institution, starting with the master Guignard, who inaugurates a modern vision of the Minas Gerais landscape, following with Nello Nuno and Annamélia, teaching artists and founders of the FAOP art school, and with their students Jorge dos Anjos and Gélcio Fortes, who became professors. The study of FAOP's memory and history will seek to answer the question of how this space acts in perceiving the landscape of the historic city. Does the contact, and the making of art, contribute to the protection of the landscape and the production of the common? To do so, it investigates the interactions between body, landscape and history through artistic expressions. Studies on the history of FAOP and its role in the life of the community are rare. Thus, this dissertation aims to fill these gaps and contribute to the understanding of how the presence of art, artists and training in the area contribute to the approximation and preservation of cultural heritage territories. The research starts from the notion of “landscape” and its history and enters the territory of Ouro Preto through the vision of the artist-teachers. In order to understand the interaction between art, the landscape and teaching, it analyzes interviews with the artist-teachers and the artist-students-teachers. The testimonies indicate how the artist's thinking establishes the teaching methodology, the structure of FAOP and the relationships between student and city and how it relates to those factors. The selection and analysis of works and the comparative study seek to identify space-time continuities and transformations on Ouro Preto's art history.